PERSEPSI MAHASISWA AKUNTANSI TERHADAP PENERAPAN MATA KULIAH AKUNTANSI FORENSIK DALAM KURIKULUM JURUSAN AKUNTANSI DI UNIVERSITAS (STUDI KASUS PADA UNIVERSITAS 17 AGUSTUS 1945 SURABAYA) (Universitas 17 Agustus 1945 Surabaya, 2022)
This research aims to analyze the perception of accounting students towards forensic accounting courses in the curriculum of the accounting major at the University. Entering forensic accounting courses in accounting departments is the answer to the development of the forensic accountant profession in several Government and KAP agencies that require quality labor produced by universities to produce graduates who are ready to enter the workforce. The object of research is a student in the accounting department. This research is an empirical study of purposive sampling methods in data collection. The data was obtained by distributing questionnaires of 100 pure students and students of workers in the accounting department who had taken forensic accounting courses at the University of August 17, 1945 Surabaya. Data analysis conducted with pls program version 2.0 research results obtained the influence of perception of students majoring in accounting University August 17, 1945 by 90% on forensic accounting courses in the curriculum at the college is very close. The results of hypothesis testing showed that all independent variables had a positive influence on forensic accounting courses